Geomechanical parameters in granite formations obtained by a knowledge based system - Miranda, Tiago F. S. (2004)
In this paper a computational system for the calculation of geomechanical parameters for modeling of underground structures in granite formations is presented. This system called GEOPAT uses artificial intelligence techniques. After an important research of the rock and soil masses characterization methodologies and its behavior, a knowledge based system (KBS system) was developed. This system contains well systematized and organized knowledge about the calculation of geomechanical parameters in rock, soil and heterogeneous formations. To congregate and organize specialists knowledge causal nets have been established. The interfaces are interactive and the system uses Visual Basic, KAPPA-PC and Excel platforms. GEOPAT aims to be an important tool for decision support. This system was applied to an underground structure and simulation performance behavior compared with that obtained by using design parameters.